Use of aircraft in ocean alkalinity enhancement - Gentile, Elisa; Tarantola, Fabio; Lockley, Andrew; Vivian, Chris; Caserini, Stefano (Science of The Total Environment, 2022)
Ocean Alkalinity Enhancement (OAE) is a proposed Negative Emissions Technology (NET) to remove atmospheric CO2 through the dispersion of alkaline materials (e.g.: calcium hydroxide, slaked lime, SL) into seawater, simultaneously counteracting ocean acidification. This study considers aircraft discharge of SL and its consequent dry deposition, extending to the marine environment a technique used in freshwater. A feasibility analysis assesses potential, costs, benefits, and disadvantages, considering scenarios with different assumptions on aircraft size, discharge height and duration, and wind conditions.Due to the small size of SL particles (median diameter 9 mu m), the dispersion from aircraft is highly enhanced by wind drift; the smallest SL particles may drift thousands of kilometres, especially if discharged from elevated altitudes. This could pose problems related to powders particles settling on remote lands.Although calcium hydroxide maximum concentration into water (from 0.01 to 82 mg L-1) is for almost all the scenarios lower than the most stringent threshold for the ecosystem impacts on a 96-h exposure, the ecologically sensitive sea surface microlayer (SAIL) should be considered in detail.The high CO2 emissions of the Landing to Take-Off Cycle (LTO) of the aircraft and their limited payload lead to a significant CO2 penalty, ranging in analysed scenarios between 28% and 77% of the CO2 removal potential; very fast discharge could reduce the penalty to 11% -32%. Preliminary cost analysis shows that the cost of the SL discharge through aircraft is high, between (sic) 30 and (sic) 1846 per ton of CO2 removed (neglecting the lime cost), substantially higher than the cost for discharge by surface vessels resulting from previous studies, which restricts the practical use of this strategy.